Mobile and wireless technologies 2016 - Kim, Kuinam J.; Wattanapongsakorn, Naruemon; Joukov, Nikolai (Lecture notes in electrical engineering, 2016)
This book presents the peer-reviewed contributions of ICMWT2016, an international conference devoted to mobile and wireless technology.